Effect of Cooling Header on the Hydrocarbon Fuel Flow Distribution in a Regenerative Cooling Channel. (8th September 2022) - Yin, Liang; E, Jiaqiang; Ding, Jie
Abstract : Regenerative cooling technology is the most widely used cooling technology in liquid rocket engines, and flow distribution is very important for regenerative cooling heat transfer. In this work, the flow distribution characteristics of Z -type parallel channels were studied through numerical simulation, and the effects of flow area ratio, inlet header shape, and inlet aspect ratio were analyzed. Results showed that changing the inlet cooling header can improve the uniform distribution of flow rate effectively. The nonuniformity coefficient and fuel temperature varied with change in the flow area ratio, inlet header shape, and inlet aspect ratio. The maximum temperature of the wall decreased from 1334.52 K to 1220.61 K when the flow area ratio was changed from 1 to 0.25. An appropriate decrement in the inlet header shape was beneficial to the uniform flow distribution. The inlet aspect ratio should be reduced properly to ensure that each channel experiences similar pressure drop. This research has a certain reference value for the structural design of regenerative cooling channels.